Regulation of varicella-zoster virus gene expression in human T lymphocytes. - Perera, L P (1992)
Varicella-zoster virus (VZV), a neurotropic alphaherpesvirus, is the etiologic agent of chicken pox and shingles (zoster) in humans. Using an in vitro transient expression assay, we have evaluated the ability of the putative immediate early VZV genes, ORF4, ORF61, and ORF62 (the analogs of the herpes simplex virus alpha 27, alpha 0, and alpha 4 genes, respectively), to modulate the expression of VZV genes of different putative kinetic classes in a human T lymphocyte cell line. These cells are of the type in which VZV can be readily detected in the viremic phase of human infection. We present evidence to indicate that, in this system, the gene product of ORF62 (IE62) is a major regulatory protein in VZV and is capable of activating VZV genes of all putative kinetic classes. In addition, we demonstrate that the gene product of ORF4 and, unlike the apparent situation in Vero cells, the gene product of ORF61 may play an accessory regulatory role in synergizing the activation of VZV genes induced by the gene product of ORF62 in human T lymphocytes.